2023
DOI: 10.3390/d15030331
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Suppression of Red Imported Fire Ants (Solenopsis invicta) Has Little Impact on the Survival of Eggs to Third Instar of Spring-Generation Monarch Butterflies (Danaus plexippus) Due to Buffering Effects of Host-Plant Arthropods

Abstract: The eastern migratory population of the monarch butterfly (Danaus plexippus) has shown evidence of declines in recent years. During early spring, when the population is at its smallest, red imported fire ants (RIFA) (Solenopsis invicta) have been implicated as having devastating effects on monarch egg and larval survival, but there are no conclusive experimental data to support this contention. The purpose of this study was to determine the effect of RIFA on the survival of spring monarch eggs to third instar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Calvert (2004) later reported that monarch larval survival is higher within small exclosures (~20 m 2 ) treated for fire ants than outside. In contrast, other researchers in Texas reported that a higher percentage of monarchs survived to third instars closer to red imported fire ant mounds than farther away from fire ant mounds (Hudman 2018) and that fire ants had no significant effect on fifth instar survival (Scott 2019). Monarch survival from egg to fifth instar is very low (7–10%; Nail et al 2015) even in areas without fire ants, so it is not clear if fire ants decreased monarch survival, or if fire ants removed or replaced other predators (Calvert 2004, Hudman 2018).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Calvert (2004) later reported that monarch larval survival is higher within small exclosures (~20 m 2 ) treated for fire ants than outside. In contrast, other researchers in Texas reported that a higher percentage of monarchs survived to third instars closer to red imported fire ant mounds than farther away from fire ant mounds (Hudman 2018) and that fire ants had no significant effect on fifth instar survival (Scott 2019). Monarch survival from egg to fifth instar is very low (7–10%; Nail et al 2015) even in areas without fire ants, so it is not clear if fire ants decreased monarch survival, or if fire ants removed or replaced other predators (Calvert 2004, Hudman 2018).…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, other researchers in Texas reported that a higher percentage of monarchs survived to third instars closer to red imported fire ant mounds than farther away from fire ant mounds (Hudman 2018) and that fire ants had no significant effect on fifth instar survival (Scott 2019). Monarch survival from egg to fifth instar is very low (7–10%; Nail et al 2015) even in areas without fire ants, so it is not clear if fire ants decreased monarch survival, or if fire ants removed or replaced other predators (Calvert 2004, Hudman 2018). Alternatively, Nixon (2019) reported that monarch survival was higher on plants with higher densities of alternative prey available.…”
Section: Discussionmentioning
confidence: 84%